Impact of Massachusetts Health Reform on Inpatient Care Use: Was the Safety‐Net Experience Different Than in the Non‐Safety‐Net?. (8th August 2016) - Hanchate, Amresh D.; McCormick, Danny; Lasser, Karen E.; Feng, Chen; Manze, Meredith G.; Kressin, Nancy R.
Abstract : Objective: Most inpatient care for the uninsured and other vulnerable subpopulations occurs in safety‐net hospitals. As insurance expansion increases the choice of hospitals for the previously uninsured, we examined if Massachusetts health reform was associated with shifts in the volume of inpatient care from safety‐net to non‐safety‐net hospitals overall, or among other vulnerable sociodemographic (racial/ethnic minority, low socioeconomic status, high uninsured rate area) and clinical subpopulations (emergent status, diagnosis). Data Sources/Study Setting: Discharge records for adults discharged from all nonfederal acute care hospitals in Massachusetts, New Jersey, New York, and Pennsylvania 2004–2010. Study Design: Using a difference‐in‐differences design, we compared pre‐/post‐reform changes in safety‐net and non‐safety‐net hospital discharge outcomes in Massachusetts among adults 18–64 with corresponding changes in comparisons states with no reform, overall, and by subpopulations. Principal Findings: Reform was not associated with changes in inpatient care use at safety‐net and non‐safety‐net hospitals across all discharges or in most subpopulations examined. Conclusions: Demand for inpatient care at safety‐net hospitals may not decrease following insurance expansion. Whether this is due to other access barriers or patient preference needs to be explored.